Cotton Fabric-Lined Egg Tray Earmuff Intervention for Noise-Induced Hearing Loss - Widjanarti, Maria Paskanita; Ismayenti, Lusi; Kartika, Ayu Prima; Azzahra, Nirwana Putri; Rha, Warda Yussy; -, Sumardiyono; Suratna, Farhana Syahrotun Nisa; gustav, Jordan syah; Rinawati, Seviana; Atmojo, Tutug Bolet; Utomo, Bekti (Sekolah Vokasi Universitas Gadjah Mada, 2025)
Background: Weaving workers are exposed to noise exceeding the Threshold Limit Value (TLV), putting them at risk of noise-induced hearing loss. Egg trays and cotton fabric have noise absorption capabilities. These materials have potential as eco-friendly noise dampening materials in earmuffs.Objective: This study aimed to analyze the effect of using cotton fabric-lined egg trays in earmuffs on noise-induced hearing loss among workers.Methods: The effectiveness of earmuffs was tested through a quasi-experimental design with pretest and posttest approaches in intervention and control groups with 82 respondents. Noise Induced Hearing Loss (NIHL) was measured through audiometric examination of both ears. Data were analyzed using Somers'd, Marginal Homogeneity, and Kolmogorov-Smirnov tests.Results: The modified earmuffs were able to reduce noise by up to 34 dB with an effective NRR of 20.25 dB. The experimental group experienced a significant decrease in NIHL (p=0.000), while the control group experienced an increase in NIHL. Age and length of employment had significant effects (p<0.05). There was a significant posttest difference between the experimental and control groups (p=0.008).Conclusion: Modified earmuffs containing cotton fabric-lined egg trays proved effective in reducing noise. The use of earmuffs by workers reduced the risk of Noise Induced Hearing Loss (NIHL).